Flow distribution and wave propagation in arterial systems with anastomoses - Kizilova, N.; Sechin, R.P. (My University, 2005)
Blood flow and wave propagation in the systems of compliant tubes filled with a fluid have been examined as a model of the systemic circulation and the intraorgan arterial networks have been modeled as Windkessel elements or regular treelike branching structures. Real intraorgan vasculatures possess some geometrical regularity and can be modeled as fractal-like trees. Nevertheless blood flow in the real beds and their self-similar models have some differences. Moreover real vasculatures often have anastomoses which provide additional pathways for blood flow and wave propagation and reflection. Arterial beds in the small and large intestine, in stomach and limbs have arterial anastomoses that influence input admittance spectra of the beds in comparison with the tree-like systems.
Keywords: Blood flow; intraorgan arterial networks; wave propagation